Moderate Mocha Coffee Consumption Is Associated with Higher Cognitive and Mood Status in a Non-Demented Elderly Population with Subcortical Ischemic Vascular Disease - Fisicaro, Francesco (Nutrients, 2021)
To date, interest in the role of coffee intake in the occurrence and course of age-related neurological and neuropsychiatric disorders has provided an inconclusive effect. Moreover, no study has evaluated mocha coffee consumption in subjects with mild vascular cognitive impairment and late-onset depression. We assessed the association between different quantities of mocha coffee intake over the last year and cognitive and mood performance in a homogeneous sample of 300 non-demented elderly Italian subjects with subcortical ischemic vascular disease. Mini Mental State Examination (MMSE), Stroop Colour-Word Interference Test (Stroop T), 17-items Hamilton Depression Rating Scalfe (HDRS), Activities of Daily Living (ADL), and Instrumental ADL were the outcome measures. MMSE, HDRS, and Stroop T were independently and significantly associated with coffee consumption, i.e., better scores with increasing intake. At the post-hoc analyses, it was found that the group with a moderate intake (two cups/day) had similar values compared to the heavy drinkers (≥three cups/day), with the exception of MMSE. Daily mocha coffee intake was associated with higher cognitive and mood status, with a significant dose-response association even with moderate consumption. This might have translational implications for the identification of modifiable factors for vascular dementia and geriatric depression.